Design of Banking Products focused on Financing the University Education in the Czech Republic - Růžičková, Lucie; Hnilica, Jiří, 1976-; Dvořák, Jaroslav; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2011)
This thesis deals with the situation in financing of tertiary education from both governmental and student perspective. Its objective is to find an efficient system of student support with focus on student loans that would be applicable in the Czech Republic, would promote an equal access to higher education also to students from lower socio-economic classes and at the same time would enable to increase cost-sharing in Czech tertiary education. The designed concept of student loans is based on best practices from selected European countries (Netherlands, United Kingdom and Hungary) in the background of proposed reform of Czech tertiary education. Finally, the concept is validated in a case study dealing with financing of the International Management master's programme at the University of Economics, Prague.
Vedoucí práce: Jiří Hnilica
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2011
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2011
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses